Policy interactions, uncertainty, and credit cycles in financial dynamic stochastic general equilibrium models - Mustafayev, Elchin (2018)
This dissertation joins a vibrant conversation in macroeconomics about the role of financial frictions in business cycles spurred on by the recent financial crisis. Our proposed study contributes to this lively debate in a fundamental way by putting forward two DSGE models. Firstly, we consider a DSGE model which accounts for the financial sector and assumes a distorted steady state. Unlike in studies where the welfare effects of distinct policy bodies i.e. the central bank and the macroprudential institution are not tracked, in our proposed model we derive welfare-based loss functions that trace associated inefficiencies emerging from both nominal and financial distortions. Therefore, to the best of our knowledge, this model is the first to consider welfare-based mandates to the central bank and the macroprudential institution that targets related inefficiencies. In addition, a key innovation of this model is the use of such welfare-based mandate in a game-theoretical framework. Secondly, we introduce a DSGE model, which in addition to financial frictions, is augmented with stochastic volatility and nominal rigidities. This model is then used to assess the effectiveness of conventional, unconventional monetary policies and macroprudential policies in mitigating the effects of disturbances in the presence of risk shocks. To the best of our knowledge, this second model is the first to analyse the effectiveness of unconventional monetary policy and macroprudential policies with stochastic volatility. Furthermore, another key novelty of our research is the analysis of the interactions between three policy options, namely conventional, unconventional monetary and macroprudential policies.